Purification and Characterization of Two Thermostable Xylanases from a Halotolerant Bacillus Sp. asc6ba Isolated from Salar de Ascotán, Atacama Desert - Blamey-Alegria, J (Springer Japan, 2021)
Two extracellular xylanases, denominated X2 and X3, were purified and characterized from the halotolerant bacterium Bacillus sp. Asc6BA isolated from “Salar de Ascotán” in the Atacama Desert. Xylanases were purified by anion exchange, cation exchange and size exclusion liquid chromatography. Xylanase X2 and X3 were purified ~ 690-fold and ~ 629-fold, respectively, compared to the concentrated extracellular fraction with a final specific activity of 169 and 154 u mg−1, respectively. Optimal conditions of pH and temperature of xylanolytic activity were 6.0 and 60 °C for X2 and 7.0 and 60 °C for X3. Half-life of X2 xylanase was 30 min at 50 °C, while X3 xylanase was remarkably more thermostable, retaining more than 70% of its activity after 32 h of incubation at 50 °C. X2 exhibited Km, Vmax and kcat values of 7.17 mg mL−1, 1.28 mM min−1 mg−1 and 425.33 s−1, respectively. X3 exhibited Km, Vmax and kcat values of 6.00 mg mL−1, 19.25 mM min−1 mg−1 and 82,515 s−1, respectively. In addition to their thermal stabilities, these enzymes were shown to be resistant to freeze-drying. These stability properties, in addition to the ability of these enzymes to be active in a wide range of temperatures and pHs, make these xylanases good candidates for industrial applications. © 2021, Springer Japan KK, part of Springer Nature.